تقييم وتقدير حجم قطرات المطر باستخدام جهاز المحاكاة المطرية ودوره في تحسين النمذجة الهيدرولوجية (Comprehensive Journal of Science, 2025)
This study aims to evaluate the accuracy of estimating raindrop size using a rainfall simulator as an effective method in hydrological and meteorological research. There is a need to assess the performance and efficiency of these devices under the local conditions of arid and semi-arid regions. The methodology involves designing devices to conduct simulation experiments for different rainfall rates, with precise calibration of the device to ensure realistic simulation of natural raindrops in terms of size and distribution. Research results confirm that properly calibrated devices are capable of producing droplets with sizes ranging from (0.3 – 2.7) mm, which aligns with the calibration results for droplet size (0.4-2.7) mm in the study. This confirms the success of the simulation, as it falls within the specified range for natural raindrops. Furthermore, the arithmetic mean of the Christiansen Uniformity Coefficient (CU) for the nozzles at a height of 3m shows a clear improvement, with a high percentage of 22.12%, compared to the uniformity coefficient at a height of 1.5m Calculations of central tendency and dispersion measures indicate that the distribution tends to skew negatively towards larger values, as the mode (2.5) is greater than the mean (1.67), which is less than the median (1.7). Meanwhile, the standard deviation (0.68) shows that the sizes vary acceptably around the mean, indicating natural variation in the values and that they are not concentrated around a single value. The value of the coefficient of determination (R²) equals (0.98-0.97), confirming a high linearity of the relationship, which explains the change in flow rate with the change in operating pressure. The study also highlights the importance of these accurate data in improving hydrological models and weather forecasts and provides recommendations for future research to enhance measurement accuracy and integrate modern technologies.
Keywords: Rainfall simulation; raindrop size; hydrological modeling; water erosion; water resource management; calibration